Canine Cystitis Caused by Salmonella enterica subsp. enterica - de Oliveira, Raylson Pereira; Sobral da Silva, Débora Mirelly; Santos Ferreira, Maria de Nazaré; Coutinho Moura, Camila Maria; Freitas Dias, Rômulo Francelino; Varejão da Silva, Maria Goretti; Pinheiro Junior, José Wilton; Mota, Rinaldo Aparecido (Acta Scientiae Veterinariae, 2019)
Background: Urinary tract infection in dogs is usually associated with the presence of bacteria, with a higher prevalence of Gram-negative bacteria, represented mainly by enteric bacteria such as Escherichia coli and Proteus spp., followed by Gram-positive bacteria such as Staphylococcus spp., and Streptococcus spp. There are scant reports of Salmonella spp. as the causative agent of urinary tract infection in dogs. Indeed, the literature describes only a few cases, most of which involve the isolation of these bacteria in feces. This paper reports a case of canine cystitis caused by Salmonella enterica subsp. enterica in the northeast region of Brazil. Case: A female dog of the Fila Brasileiro breed, about 9 year-old, wormed but unvaccinated, was evaluated at the Veterinary Hospital of the Federal University of Pernambuco – UFRPE. The dog showed clinical signs of apathy, cachexia, polyphagia, polyuria and opacity of the crystalline lens. The dog’s owner stated that the animal was fed with commercial dog food. In the clinical exam, the patient presented pale mucosa, cachexia, absence of ectoparasites, and her rectal temperature was 39.5°C. Moreover, cardiorespiratory auscultation of the patient revealed tachycardia (190 bpm) and tachypnea (36 bpm). The owner’s main complaint was the clinical condition of frequent urination (polyuria). A urinalysis and urine culture with antibiogram were requested as complementary exams, after collecting the urine by cystocentesis. The volume obtained in the physical examination of urinalysis was 7 mL of yellow urine with a putrid smell, cloudy appearance and density of 1.024. The chemical examination revealed pH 6.5, protein (+++), bilirubin (+), normal urobilinogen and negative reactions for glycoses, ketone, nitrite and urine occult blood. Bacteriuria and pyuria were detected in a urine sediment test. Urine was cultured on blood agar and Levine agar in a bacteriological incubator at 37°C under aerobiosis, for 24 h. This culture produced an exuberant and pure growth of glossy grey bacterial colonies on blood agar and glossy colonies on Levine agar. The Gram test revealed gram-negative bacilli. The sample was subjected to biochemical tests to identify Gram-negative enterobacteria, whose results provided a presumptive identification of Salmonella species. The microbial species was identified using a VITEK 2 Compact®, and was followed by a serology test for the identification of the serogroup using a polyvalent serum, which enabled the identification of Salmonella enterica subsp. enterica. The antibiogram showed sensitivity to ciprofloxacin, gentamicin and penicillin, and resistance to amoxicillin and ampicillin. Discussion: Clinical signs of cachexia and polyuria may be related to canine urinary tract infection caused by Salmonella enterica subsp. enterica, since these symptoms had already been recorded previously in a case of a bacterial infection by the same serogroup. Isolation of Salmonella spp. in a non-selective medium was determinant in identifying these bacteria. Since these are not commensal bacteria of the canine urinary tract, their isolation in this tract indicates that they are responsible for the infection or disease, although such cases are rare. Another aspect that should be highlighted is the risk of human infection, because of the zoonotic potential of Salmonella spp., which may be transmitted by contact with dog urine. This is the first report of the isolation of Salmonella enterica subsp. enterica in a case of canine cystitis on the northeast region of Brazil, and underscores the importance of complementary diagnostic exams such as urine culture.